Current perspectives on recurrent HPV-mediated oropharyngeal cancer - Guo, Theresa; Kang, Stephen Y.; Cohen, Ezra E. W. (Frontiers in Oncology, 2022)
In the recent years, the prevalence of HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) has increased significantly. Currently, nearly 80-90% of all oropharynx tumors are HPV-positive. In addition, it is now recognized that HPV-positive tumor status is associated with good prognosis and improved response to chemoradiation. However, within this setting, there are still patients with HPV-positive OPSCC who will experience recurrence. With the increasing incidence of HPV-mediated OPSCC, recurrent HPV disease is also becoming more prevalent and there is an increasing need to understand the unique presentation and treatment of recurrent HPV-mediated disease. In this review, we will discuss epidemiology of recurrent HPV-positive OPSCC, role of surgical salvage, re-irradiation, and the role of upcoming novel treatments and immunotherapy. Historically, recurrent oropharyngeal disease has been associated with poor prognosis and high morbidity. However, recent advances have transformed the landscape for salvage treatment of HPV-mediated OPSCC. Liquid biomarkers offer potential for early detection or recurrence, robotic techniques may reduce morbidity of surgical salvage, improvements in re-irradiation approaches reduce toxicities, and novel immune based therapies on the horizon are offering promising results. These advances combined with the improved prognosis of HPV-positive disease offer to transform our approach to recurrent disease of the oropharynx.